Cultural Identity in the Case-Law of the Human Rights Committee - Stryjkowska, Sylwia (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2017)
The aim of the article is to present the jurisprudence of the Human Rights Committee on Article 27 of the International Covenant on Civil and Political Rights concerning the rights of persons belonging to ethnic, religious and linguistic minorities. Therefore, the study examines the underprivileged position of minorities within States and focuses on their will to survive as a distinct culture. Examination of the aforementioned caselaw provides an insight into the Committee’s understanding of the concept of cultural identity.